Diagnosis incidence of autism spectrum disorders is underestimated in Australian children, and there are inequalities in access to diagnosis and treatment services: a data linkage study of health service usage - Mallitt, Kylie-Ann; Jorm, Louisa R (International Journal of Population Data Science, 2018)
Introduction The prevalence and diagnosis incidence of autism spectrum disorders (ASD) are difficult to determine. Estimates of ASD burden in Australia are produced from sample surveys of disability, and government records of welfare disability payments. While disability does affect many people with ASD, ASD itself is not a disability. Objectives and Approach For our retrospective population-based cohort study of breast cancer survivors diagnosed from 2007 to 2010 in British Columbia (BC), 2007-2011 in Manitoba (MB), 2007-2010 in Ontario (ON), and 2007-2012 in Nova Scotia (NS), we linked provincial cancer registries, clinical and health administrative databases, and followed cases alive at 30 months post-diagnosis to five years from diagnosis. For each province, we calculated percent adherence, overuse, and underuse of recommended follow-up care, including surveillance for recurrent and new cancer, surveillance for late effects, and general preventive care. We also examined variation among provinces and over time. Results Survivor numbers were 23,700 (ON), 9493 (BC), 2688 (MB), and 2735 (NS). Annual oncologist visit guideline compliance varied provincially (e.g. Year 2 ON=32.7%, BC=15.0%). For most provinces and follow-up years, the majority of survivors had fewer oncologist visits than recommended. However, survivors had additional annual breast cancer-related visits to a primary care provider. Surveillance breast imaging guideline compliance was high (e.g. Year 2, ON=81.1%, MB=72.0%, NS=52.8%, BC =49.7%), with rates declining in ON and MB (to approximately 64%), but increasing in NS and BC (to approximately 58%) by Year 5. Overuse of breast imaging was identified in NS (9.1%-20.7% overuse in follow-up years 2-5). As per the guideline, 72.9%-79.7% (Years 2-5) of BC survivors had no imaging for metastastic disease, highest among all provinces. Conclusion/Implications The diagnosis incidence of ASD in Australian children is higher than previously estimated. The prevalence of ASD is therefore also underestimated. Multidisciplinary ASD assessment and treatment services are underutilised, likely due to out-of-pocket co-payments reducing affordability. These findings have significant implications for government health service planning for ASD.